Overwintering of reproductively mature females of a pro‐ovigenic parasitic wasp, Leptopilina heterotoma (Hymenoptera: Figitidae). Issue 3 (25th June 2019) - Kimura, Masahito T.
Abstract: Leptopilina heterotoma is a Drosophila parasitoid mainly occurring in temperate regions, and females of this species are pro‐ovigenic (i.e. all or nearly all of their lifetime eggs are already mature at emergence). Here I investigated how L. heterotoma overwinters in Sapporo, Japan, a cool temperate region, by outdoor and laboratory experiments. Females of this species had mature eggs at emergence as expected, and they did not resorb eggs even if they were exposed to cold or starvation. Nevertheless, females were able to overwinter, and post‐overwintering females retained parasitization capacity. In this species, thus, adult overwintering is not associated with reproductive diapause. However, females grown in late autumn or at low temperatures (e.g. 5°C) had a fewer number of mature eggs and higher winter survival. At low temperatures, female larvae could save energy by reducing egg production and allocate the saved energy to expenditure for overwintering. In contrast to females, males and pre‐adult individuals were not able to overwinter. Abstract : Leptopilina heterotoma is a Drosophila parasitoid mainly occurring in temperate regions. Adult females of this species overwinter without entering reproductive diapause. In contrast, males are not able to overwinter.